2000
DOI: 10.1021/jp001294d
|View full text |Cite
|
Sign up to set email alerts
|

Protein Adsorption at Interfaces Detected by Second Harmonic Generation

Abstract: We show that second harmonic (SH) spectroscopy, an intrinsically surface-selective technique, can be used to monitor protein (cytochrome c) adsorption to silica surfaces and negatively charged supported phospholipid bilayers. The origin of the SH signal is due to the effect of the adsorbed protein on the water molecules polarized near the charged interface. Although the protein does not contribute its own SH signal, its binding to the glass surface or the membrane reduces the polarization of the interfacial wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
135
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(140 citation statements)
references
References 15 publications
5
135
0
Order By: Relevance
“…However, it has been shown that a decrease of the overall SHG intensity from the interface can also be observed as for example in the case of cytochrome c if the contribution of a static dc-field is taken into account. 38 In the present study, the SHG increase appeared on a much faster time scale than the corresponding surface pressure (20 min versus 2 h respectively after gp41W injection). The surface pressure delay likely underlines already internal re-arrangements within the gp41W upon adsorption as compared to the bulk aqueous phase conformation.…”
Section: A Adsorption Kinetics Of Gp41w To the Neat Air/water Interfacesupporting
confidence: 43%
“…However, it has been shown that a decrease of the overall SHG intensity from the interface can also be observed as for example in the case of cytochrome c if the contribution of a static dc-field is taken into account. 38 In the present study, the SHG increase appeared on a much faster time scale than the corresponding surface pressure (20 min versus 2 h respectively after gp41W injection). The surface pressure delay likely underlines already internal re-arrangements within the gp41W upon adsorption as compared to the bulk aqueous phase conformation.…”
Section: A Adsorption Kinetics Of Gp41w To the Neat Air/water Interfacesupporting
confidence: 43%
“…Second-order nonlinear spectroscopies with their intrinsic surface sensitivity [3] have provided important molecular-level insights into biological surface systems [4]. In particular, VSFG [5] has been used to probe DPPC phospholipid layers at the liquid-liquid interface as well as the kinetics of bilayer formation from vesicle rupture [6] by monitoring C -H stretch vibrations of both CH 2 and terminal CH 3 groups in the alkyl chain.…”
mentioning
confidence: 99%
“…This value is comparable to or less than that used in other SHG or SFG studies involving polymers. 18,20,26 Additionally, it is important that the sample is not heated by the laser during the experiment as this would affect the molecular dynamics. The lack of absorbance bands at the laser wavelength is a benefit in this respect, and the laser power levels used in this study are less than levels that have been verified to prevent heating of thin polymer samples.…”
Section: Methodsmentioning
confidence: 99%